2009
DOI: 10.1186/1477-7827-7-54
|View full text |Cite
|
Sign up to set email alerts
|

Women with endometriosis improved their peripheral antioxidant markers after the application of a high antioxidant diet

Abstract: Background: Oxidative stress has been identified in the peritoneal fluid and peripheral blood of women with endometriosis. However, there is little information on the antioxidant intake for this group of women. The objectives of this work were 1) to compare the antioxidant intake among women with and without endometriosis and 2) to design and apply a high antioxidant diet to evaluate its capacity to reduce oxidative stress markers and improve antioxidant markers in the peripheral blood of women with endometrio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
86
1
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(104 citation statements)
references
References 33 publications
1
86
1
7
Order By: Relevance
“…However, intake of long-chain omega-3 fatty acids was associated with a lower risk of endometriosis Stacey A. Missmer et al,(2010) 21 . Although a trend for a decreased risk could be observed in Parazzini et al,(2003) 28 while a complete absence of any association was found by Britton Traberta et al,(2010) 20 .…”
Section: Endometriosis and Fat Intakementioning
confidence: 99%
See 1 more Smart Citation
“…However, intake of long-chain omega-3 fatty acids was associated with a lower risk of endometriosis Stacey A. Missmer et al,(2010) 21 . Although a trend for a decreased risk could be observed in Parazzini et al,(2003) 28 while a complete absence of any association was found by Britton Traberta et al,(2010) 20 .…”
Section: Endometriosis and Fat Intakementioning
confidence: 99%
“…Stacey A. Missmer et al,(2010) 21 , suggested that intake of trans-unsaturated fats was associated with a higher risk of endometriosis . Intakes of saturated fat and monounsaturated fat, were not associated with endometriosis risk.…”
Section: Endometriosis and Fat Intakementioning
confidence: 99%
“…There is one more condition to verify the connection between bodily perception and the quality of the living experience. According to research, an important predictor of disease development is low body weight (Nagle et al, 2009), and one factor supporting treatment is to keep to an antioxidant diet (Mier-Cabrera et al, 2009) and undergo moderate physical exercise (Petta, op. cit.).…”
Section: Introduction To Research: Examined Variablesmentioning
confidence: 99%
“…Moreover, a heat shock protein 70 (HSP70) family member (HSP70b′), known to be present under increased oxidative conditions, has been found in high concentrations in the blood of patients with this pathology ). Also, lower levels of antioxidants such as vitamins A, C, E, zinc, and copper were found in women with endometriosis (Mier-Cabrera et al 2009). Finally, vitamin E levels were significantly decreased in patients with endometriosis before the beginning of ovulation induction, perhaps due to the fact that antioxidants are consumed during oxidation reactions.…”
Section: Ros and Fertility-related Diseases Endometriosismentioning
confidence: 99%
“…A high antioxidant diet, containing vitamins A, C, and E, originated an increase in antioxidant enzyme activity as well as a decrease in oxidative stress markers after 2 months of intervention (Mier-Cabrera et al 2009). Moreover, ad-ministration of antioxidants (vitamin C and E) was concluded to reduce chronic pelvic pain and inflammatory markers in the peritoneal fluid in women with endometriosis (Santanam et al 2013).…”
Section: Ros and Fertility-related Diseases Endometriosismentioning
confidence: 99%